Kinetic characteristics of distance running on downhill slope - Yokozawa, T.; Fujii, N.; Ae, M. (International Journal of Sport & Health Science, 2005)
The purpose of this study was to investigate kinetic characteristics such as ground reaction forces (GRFs) and joint torques of the lower limb joints in downhill running for distance runners on overground. Six male distance runners were asked to run at three running speeds (3.3, 4.2, and 5.0 m/s) on the slopes of different grades (0, -3.2, -6.4, and -9.1 %) in which two force platforms were mounted. A two dimensional link model was used to calculate joint torques and joint powers of the lower limb joints. In spite that the downward velocity of the CG at the foot contact increased consistently as the grade increased, the impact peak of vertical GRF and the peak loading rate defined as maximum rate of change of the vertical GRF did not increase consistently as the grade increased. The runners on steep downhill conditions would be able to avoid excessive impact load by contacting with the ground in more extended hip position and increasing knee flexion velocity after the foot contact. The negative power of the knee after the foot contact was larger for -9.1 % downhill than the level condition, which revealed the eccentric load on the knee extensors increased in the steep downhill condition. The hip extensors exerted negative power with hip flexion just after the foot contact in -6.4 and -9.1 % downhill conditions so that the runners could absorb the impact force and mechanical energy.